Meta Analysis: Factors Affecting Alcohol Consumption in Adolescents - Ihsan Hanif; Ardiana Mardiah; Rachmawaddah Yolanda; Bhisma Murti; Siti Mar'atul Munawaroh (Journal of Health Promotion and Behavior, 2024)
Background: Since alcohol is obtained easily, so it tends to be widely abused. The factors that cause a teenager to consume alcohol are individual factors/individual personality, and environmental factors. This study aims to estimate the factors that affect alcohol consumption in adolescents. Subjects and Method: This study used systematic review and meta-analysis using PICO. Population: adolescents. Interventions: drinking parents, drinking friends, smoking. Comparison: non-drinking parents, non-drinking friends, non-smoking. Result: alcohol consumption. The articles used in this study were derived from 2 databases, namely Google Scholar and Science Direct. The article's keywords were ""teenager" AND "drinking parents" AND "drinking friends" AND "smoke" AND “alcohol consumption". The articles included in this study were full paper articles, cross-sectional study design, publication year ranged from 2019-2023 and the measure of association used was Adjusted Odds Ratio. The articles were analyzed using the Review Manager 5.4 application. Results: Seven cross-sectional studies showed that drinking friends increased alcohol consumption by 5.09 times compared to non-drinking friends, and the result was statistically significant (aOR=5.09; CI 95%= 2.64 to 9.81; p= 0.001). Seven cross-sectional studies showed that drinking parents increased alcohol consumption by 1.99 times compared to non-drinking parents, and the result was statistically significant (aOR=1.99; CI 95%= 1.50 to 2.64; p= 0.001). Seven cross-sectional studies showed that smoking can increase alcohol consumption by 2.09 times compared to nonsmoking, and the result was statistically significant (aOR=2.09; CI 95%= 1.32 to 3.30; p= 0.001). Conclusion: Smoking-adolescents, drinking parents, and drinking friends increase their likelihood of consuming alcohol.